Development and evaluation of miniature stirling engine integrated with a DC generator for charging mobile devices - Liu, Darren Chon Yon (2024)
Utilization of Stirling engines is the main focus of this study for portable power generation, offering a versatile solution for areas lacking access to power grids. The Stirling engine’s ability to harness various heat sources, including solar energy and biomass, presents a promising avenue for sustainable energy production. However, despite theoretical predictions suggesting high efficiency comparable to the Carnot cycle, practical implementations exhibit constrained thermal efficiency, posing a significant challenge for electricity generation applications. This study aims to address this discrepancy by identifying and recommending viable solutions to enhance the efficiency and power output of small-scale Stirling engines. By bridging the gap between theory and practice, this research seeks to unlock the full potential of Stirling engines as reliable and efficient energy solutions, contributing to sustainable development and energy access in underserved regions. The results presented offer a comprehensive comparison of Stirling engine output power across various configurations. Notably, the analysis reveals the superior performance of a Stirling engine equipped with a larger diameter titanium displacer and a 100˚ phase angle, underscoring the importance of optimization in maximizing power output. Overall, this study contributes to a deeper understanding of Stirling engine dynamics and provides insights into strategies for improving efficiency and performance. By addressing key challenges and offering practical solutions, the study paves the way for the broader adoption of Stirling engines as integral components of sustainable energy systems.